2020
DOI: 10.12688/f1000research.23598.1
|View full text |Cite
|
Sign up to set email alerts
|

Differential dynamics of early stages of platelet adhesion and spreading on collagen IV- and fibrinogen-coated surfaces

Abstract: Background: Upon wound formation, platelets adhere to the neighboring extracellular matrix and spread on it, a process which is critical for physiological wound healing. Multiple external factors, such as the molecular composition of the environment and its mechanical properties, play a key role in this process and direct its speed and outcome. Methods: We combined live cell imaging, quantitative interference reflection microscopy and cryo-electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
2
1
0
Order By: Relevance
“…Moreover, microtubules are often found in the pseudopodia protrusions, in addition to the actin filaments. This observation is in agreement with a recent study that identified microtubules in over 30% of platelet protrusions (53).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Moreover, microtubules are often found in the pseudopodia protrusions, in addition to the actin filaments. This observation is in agreement with a recent study that identified microtubules in over 30% of platelet protrusions (53).…”
Section: Discussionsupporting
confidence: 94%
“…Analysis of cryotomograms revealed densities attached to the extracellular phase of the plasma membrane ( Fig. 1 C , arrowheads, Inset ), while the cytoplasm contains cytoskeleton filaments (i.e., actin filaments and often microtubules), as previously described ( 52 , 53 ). Cryo-ET analysis of mouse platelets deficient in the α IIb β 3 integrin ( 54 ) shows a smooth membrane lacking extracellular densities ( SI Appendix , Fig.…”
Section: Resultssupporting
confidence: 77%
“…3 ), with no cells harboring localized mRNA after 2 h (Additional file 2 : Figure S3 A, C), VBT-treated cells retained the protrusion and the localized mRNA even after 3 h (Additional file 2 : Figure S3, E, G). Previous studies demonstrated that filopodia remain intact and motile after disruption of microtubule with VBT and/or NCZ [ 113 , 114 ]. Although many studies describe the transport of mRNA to cell protrusions, we could not find any publication describing the fate of mRNA after its local translation; does it undergo dispersion or degradation?…”
Section: Resultsmentioning
confidence: 99%
“…During the process of spreading, the actin cytoskeleton of platelets forms filamentous structures that associate with myosin to form actomyosin filaments that generate traction forces (4). This process is critical for stable adhesion (5)(6)(7), but there are differences in platelet spreading depending on the adhesive environment (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%